A review on valorization of spent coffee grounds (SCG) towards biopolymers and biocatalysts production. (October 2020) - Dattatraya Saratale, Ganesh; Bhosale, Rahul; Shobana, Sutha; Banu, J. Rajesh; Pugazhendhi, Arivalagan; Mahmoud, Eyas; Sirohi, Ranjna; Kant Bhatia, Shashi; Atabani, A.E.; Mulone, Vincenzo; Yoon, Jeong-Jun; Seung Shin, Han; et al.
Graphical abstract: Highlights: Spent Coffee Grounds (SCG) generation and their characterization are addressed. Overviews the innovative processes and products developed based on SCGs. Integral valorization of SCG to bioactive compounds and biopolymers mentioned. Future perspectives and challenges for SCG biorefinery is provided. Abstract: Spent coffee grounds (SCG) are an important waste product millions of tons generated from coffee consumption and could be effectively utilized for various applications due to their high organic content. SCG can be used as a potential feedstock to develop coffee–based biorefinery towards value–added products generation through various biotechnological processes. Considerable developments have been reported on emerging SCG-based processes/products in various environmental fields such as removal of heavy metals and cationic dyes and in wastewater treatment. In addition, SCG are also utilized to produce biochar and biofuels. This review addressed the details of innovative processes used to produce polymers and catalysts from SCG. Moreover, the application of these developed products is provided and future directions of the circular economy for SCG utilization.